Study of Batik effluent treatment using Moringa oleifera as coagulant-flocculant - Zuriati Khairuddin
Today, water pollution has become the greatest threat to the world because water is essential element for living organisms. Textile industry has been known for its usage of dangerous chemicals in dyes. Effluent from the textile industries is believed to gontain highly toxic contaminants which is discharged into water bodies. Many developments on the pollutant reduction methodology has been investigated and applied in the industry sector. However, the conventional technique has caused more loss because it costs a lot of money, energy, not environmental friendly and producing toxic by-product. Thus, this leads to new cost wise, energy safe and environmental friendly technique to be studied. In Malaysia, water pollution is not a new issue because it widely occurs in the rural areas caused by the small scale textile industries, especially for Batik industries in Terengganu. Since pre-treatment process of the effluents is not economic wise, this process is neglected by industries which worsens the quality of water. The contaminants present in the water body may also be very high, above the permissible limit allowed by the Malaysian Department of Environmental (DOE). This study focuses on improving the quality of water until it complies the limit allowed by the Malaysian Standard. There are three objectives for this study which are to characterize the quality of raw and treated Batik industry effluents, to id ntify new treatment technique using M. oleifera seed powder efficiency and to determine of M. oleifera dosage in achieving the best result of the treatment. The procedure of this study started by sampling the Batik effluent and collecting M. oleifera seed. M. oleifera seed was dried at 60°C for 24 hours and grinded into powder. M. oleifera seed powder, with 14 dosages, were then vigorously mixed followed by slow mixing in order for the coagulation to occur, in 14 different containers. The mixture of Batik effluent and Moringa oleifera was allowed to settle for 24 hours. Analysis of the treated effluent was conducted at different settlement hour. Data obtained was further statistically analyzed. From the study conducted it shows that Moringa oleifera can maintain pH in neutral values and reduce chemical oxygen demand (87.61 %), biological oxygen demand (80.19%), total suspended solids (99.89%), turbidity (98.91 %), oil and grease (99.70%) and metals (>90.0%). Cluster and discriminant analysis results prove pollutants can be minimized to comply to the DOE standard allowed with small dosage of M. oleifera, 2.5g for about 1-3 hours settling time. It can be concluded that small amount M. oleifera seed powder can be used as natural coagulant in reducing high amount of contaminants in Batik effluent efficiently.